Network Utilities in the U.S. - Sector Reforms without Privatization - Ingo Vogelsang (Center for Economic Studies and ifo Institute (CESifo), 2004)
U.S. network industry reforms led other countries in the past, but have recently run into difficulties in specific areas. In particular, the U.S. telecommunications sector was hit by a deep crisis and electricity reforms suffered under the California disaster. Part of the explanation for these difficulties stems from past successful liberalization and deregulation experiences in other areas suggesting that competition could provide large benefits to hitherto regulated utilities in local telephony and the electricity sector. Part of the explanation lies in an underestimate of the coordination problems, resulting in bad institutional design, and in the difficulty to deal with vested consumer interests.
Keywords: 330; network industries; regulation; competition; telecoms; electricity